2021
DOI: 10.3389/fphar.2021.761922
|View full text |Cite
|
Sign up to set email alerts
|

Physalin A Inhibits MAPK and NF-κB Signal Transduction Through Integrin αVβ3 and Exerts Chondroprotective Effect

Abstract: Osteoarthritis (OA) is a common articular ailment presented with cartilage loss and destruction that is common observed in the elderly population. Physalin A (PA), a natural bioactive withanolide, exerts anti-inflammatory residences in more than a few diseases; however, little is known about its efficacy for OA treatment. Here, we explored the therapeutic effects and potential mechanism of PA in mouse OA. After the in vitro administration of PA, the expression of inflammation indicators including inducible nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Proinflammatory cytokines such as IL-1β, tumor necrosis factor (TNF)-α, and IL-6 are critical mediators of articular cartilage degeneration and synovium inflammation [ 9 , 10 , 11 ]. In other studies, the nuclear factor-kappaB (NF-κB) and the mitogen-activated protein kinase (MAPK) have been suggested as alternative treatments for OA [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokines such as IL-1β, tumor necrosis factor (TNF)-α, and IL-6 are critical mediators of articular cartilage degeneration and synovium inflammation [ 9 , 10 , 11 ]. In other studies, the nuclear factor-kappaB (NF-κB) and the mitogen-activated protein kinase (MAPK) have been suggested as alternative treatments for OA [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of chondrocytes treated with IL-1β or OB or 3-MA for 24 h was determined by a CCK-8 kit. The selection of time duration of the above reagent on chondrocytes is based on previous studies by us and others ( 5 , 14 17 ). The chemical structure of OB was showed in Figures 1A, B demonstrated that the viability of chondrocytes was not significantly affected when cells were administration with 5 ng/ml IL-1β or 160 μM OB or 5 mM 3-MA for 24 h ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Studies illustrated that IL-1β can induce the decreased expression of anabolic-related proteins, such as Aggrecan and type II collagen (Collagen II), also trigger the overexpression of catabolic-related proteins, such as matrix metallopeptidase 3 (MMP3), matrix metallopeptidase 13 (MMP13), and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5). Then an imbalance of cellular anabolism and catabolism will arise, triggering the degradation of the extracellular matrix (ECM) of the cartilage and the occurrence of OA ( 5 ). Besides, IL-1β can promote the release of a large number of pro-inflammatory cytokines, which also contribute to the degradation of cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen specific pathogen-free C57BL/6J male mice were acquired from the Experimental Animal Center of Tongji Hospital. Mouse DMM OA model was established as previously described ( Lu et al, 2021 ). The mouse were anesthetized by intraperitoneal injection of pentobarbital (100 μl/10g body weight).…”
Section: Methodsmentioning
confidence: 99%